2019
DOI: 10.3389/fpsyg.2019.00505
|View full text |Cite
|
Sign up to set email alerts
|

Fostering Flexibility in the New World of Work: A Model of Time-Spatial Job Crafting

Abstract: In today’s “new world of work,” knowledge workers are often given considerable flexibility regarding where and when to work (i.e., time-spatial flexibility) and this has become a popular approach to redesigning work. Whilst the adoption of such practices is mainly considered a top-down approach to work design, we argue that successful utilization of time-spatial flexibility requires proactivity on the part of the employee in the form of time-spatial job crafting. Previous research has demonstrated that time-sp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
91
0
4

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 81 publications
(98 citation statements)
references
References 68 publications
3
91
0
4
Order By: Relevance
“…Included studies examined these three subcategories of psychological outcomes in a balanced manner: four studies explored cognitive outcomes [ 9 , 10 , 45 , 47 ], six studies explored emotional outcomes [ 9 , 10 , 22 , 46 , 47 , 48 ] and social outcomes [ 9 , 22 , 45 , 46 , 47 , 48 ], respectively. Among the cognitive outcomes, job demands were examined in two studies [ 9 , 10 ]; among the emotional outcomes, work engagement was examined in three studies [ 10 , 46 , 48 ], and employee satisfaction was examined in two studies [ 9 , 47 ]; six studies that explored social outcomes focused on communications/interactions/contacts [ 8 , 9 , 22 , 46 , 47 ] and family support [ 45 ]. Lastly, the level of NWW was measured in three studies using a five-item scale developed in collaboration with the organization (α = 0.56−0.84) [ 10 ], a ten-item scale covering the five NWW facets (α = 0.86) [ 46 ], and the total hours spent on: (i) remote access, (ii) working at home, (iii) email, and (iv) phone, which were identified after an HR-manager interview and reviewing the company’s NWW policy (α = 0.70) [ 48 ] ( Table 5 ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Included studies examined these three subcategories of psychological outcomes in a balanced manner: four studies explored cognitive outcomes [ 9 , 10 , 45 , 47 ], six studies explored emotional outcomes [ 9 , 10 , 22 , 46 , 47 , 48 ] and social outcomes [ 9 , 22 , 45 , 46 , 47 , 48 ], respectively. Among the cognitive outcomes, job demands were examined in two studies [ 9 , 10 ]; among the emotional outcomes, work engagement was examined in three studies [ 10 , 46 , 48 ], and employee satisfaction was examined in two studies [ 9 , 47 ]; six studies that explored social outcomes focused on communications/interactions/contacts [ 8 , 9 , 22 , 46 , 47 ] and family support [ 45 ]. Lastly, the level of NWW was measured in three studies using a five-item scale developed in collaboration with the organization (α = 0.56−0.84) [ 10 ], a ten-item scale covering the five NWW facets (α = 0.86) [ 46 ], and the total hours spent on: (i) remote access, (ii) working at home, (iii) email, and (iv) phone, which were identified after an HR-manager interview and reviewing the company’s NWW policy (α = 0.70) [ 48 ] ( Table 5 ).…”
Section: Resultsmentioning
confidence: 99%
“…This relatively new trend is called “New Ways of Working (NWW)” [ 6 ]. Organizations implementing NWW are characterized by a mixture of temporal flexibility (variation in the numbers of hours worked and the timing of the work; e.g., flexitime [ 7 ]), and spatial flexibility (allowing work tasks to be carried out outside the office, such as at home [ 8 ]). Therefore, NWW is commonly regarded as a work style that is flexible in time and location, supported by: (i) active use of ICT and (ii) management with clearly defined targets [ 9 ].…”
Section: Introductionmentioning
confidence: 99%
“…• Job Satisfaction and Engagement o Increasing resources and decreasing demands (Dierdorff & Jensen, 2018;Nielsen et al, 2017) • Job Satisfaction and Engagement o Informal work accommodations to family (Behson, 2002) • Job Satisfaction and Engagement o Increasing resources and decreasing demands (Demerouti et al, 2015;Nielsen & Abildgaard, 2012;Petrou et al, 2017;Tims et al, 2012) o Approach resource crafting (Bruning & Campion, 2018) o Self-initiated short break (Kühnel. Vahle-Hinz, De Bloom, & Syrek, 2017) o Authentically expressing personal identities at work (Cable, Gino, Staats, 2013) • Job Performance and Creativity o Time-spatial crafting (Wessels et al, 2019) o Informal work accommodations to family (Behson, 2002 Note: → = influences. * = longitudinal study with time lag between variables.…”
Section: Relaxationmentioning
confidence: 99%
“…Consequently, it is not always the job itself but the meaning you give to it that is important (Demerouti et al, 2015). It is also important to think about when and where you do each particular task, in order to manage your daily energy (Wessels et al, 2019). It should be noted, however, that it is also important to see work in relation to other areas of life.…”
Section: Values and Passionmentioning
confidence: 99%
“…Indeed, people may have more influence on their own life than they think. Studies have already shown the beneficial effects of both job crafting-where employees actively reframe their work physically, cognitively, and socially (e.g., Wrzesniewski and Dutton, 2001;Demerouti, 2014;Vogt et al, 2016;Wessels et al, 2019)-and leisure crafting (Petrou and Bakker, 2016;Vogel et al, 2016;Petrou et al, 2017). A recent study by Demerouti et al (2019) suggested that the beneficial implications of job crafting transcend life boundaries, which the authors state have also consequences in terms of experiencing meaning in life.…”
Section: Introductionmentioning
confidence: 99%